Does Substrate Positioning Affect the Selectivity and Reactivity in the Hectochlorin Biosynthesis Halogenase? - Timmins, Amy; Fowler, Nicholas J.; Warwicker, Jim; Straganz, Grit D.; de Visser, Sam P. (Frontiers in Chemistry, 2018)
In this work we present the first computational study on the hectochlorin biosynthesis enzyme HctB, which is a unique three-domain halogenase that activates non-amino acid moieties tethered to an acyl-carrier, and as such may have biotechnological relevance beyond other halogenases. We use a combination of small cluster models and full enzyme structures calculated with quantum mechanics/molecular mechanics methods. Our work reveals that the reaction is initiated with a rate-determining hydrogen atom abstraction from substrate by an iron(IV)-oxo species, which creates an iron(III)-hydroxo intermediate. In a subsequent step the reaction can bifurcate to either halogenation or hydroxylation of substrate, but substrate binding and positioning drives the reaction to optimal substrate halogenation. Furthermore, several key residues in the protein have been identified for their involvement in charge-dipole interactions and induced electric field effects. In particular, two charged second coordination sphere amino acid residues (Glu223 and Arg245) appear to influence the charge density on the Cl ligand and push the mechanism toward halogenation. Our studies, therefore, conclude that nonheme iron halogenases have a chemical structure that induces an electric field on the active site that affects the halide and iron charge distributions and enable efficient halogenation. As such, HctB is intricately designed for a substrate halogenation and operates distinctly different from other nonheme iron halogenases.